Obtaining natural tooth color with digital photography – clinical study on 30 patients - Culic, Bogdan; Dudea, Diana; Prejmerean, Vasile; Culic, Carina; Colosi, Horaţiu; Alb, Camelia (Medicine and Pharmacy Reports, 2014)
Objectives. The aim of this study is to determine the correct exposure compensation, in order to obtain pictures with natural teeth color characteristics using a selected camera. Methods. The maxillary arch of 30 patients was photographed using a Canon 400D digital camera with Canon 100 mm macro lenses and MR-14EX flash in standardized conditions: manual mode, f 22, 1/125 shutter speed, magnification ratio 1:2, WB – flash; using four different exposure compensation settings: 0 (A), 1/3 (B), 2/3 (C), 1 (D) for each patient. A 6 mm2 area from the buccal surface of the maxillary central incisor 1.1. was measured from the photographs using the DetColorDent 1.0. software. The CIE L*, a*, b* values were obtained. A spectrophotometer, Vita Easy Shade (Vita, Germany) was used as control, measuring the same area of the selected tooth. A second set of L*, a*, b* values was obtained and the ΔE was calculated. The ΔE values < 3.4 were considered clinically acceptable. The results were statistically analyzed using the SSPS 13.0 for Windows - Mann Whitney test. Results. The ΔE values obtained were situated in the interval 2.99-25.68. The highest number of ΔE values lower than 3.4 were obtained for the exposure compensation setting ‘C’ (56%). For this case, the mean value of ΔEC was 5.43±2.46, CI 95% = [4.41; 6.44]. There was a significant difference between ΔEC and ΔEA, ΔEB, ΔED (p≤0.001). Conclusions. The digital images obtained by using camera Canon 400D revealed natural color mainly for the exposure compensation setting ‘C’.